Genetic diversity and phylogenetic study of Ongole Grade cattle population in Central Java based on blood protein polymorphism - Dela Ayu Lestari; Sutopo Sutopo; Asep Setiaji; Edy Kurnianto (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lestari DA, Sutopo, Setiaji A, Kurnianto E. 2023. Genetic diversity and phylogenetic study of Ongole Grade cattle population in Central Java based on blood protein polymorphism. Biodiversitas 24: 617-624. This research provides useful information to reflect the genetic structure and to determine appropriate breeding strategies for the Ongole Grade cattle population in Central Java. The objectives of this research were to investigate the genetic diversity and phylogenetic relationship of the Ongole Grade cattle (Bos indicus) population in Central Java based on blood protein polymorphism. A total of 208 blood samples were collected, which belonged to 6 populations of Ongole Grade cattle in Central Java, namely Rembang, Blora, Kebumen, Semarang, Magelang, and Kudus regency. Blood protein analysis was conducted by Sodium Dodecyl Sulfate-Polyacrilamide Gel Electrophoresis (SDS-PAGE) methods to separate blood protein based on molecule weight. Results showed 4 blood protein locus were clearly identified, namely Albumin (Alb), Post Albumin (Pa), Ceruloplasmin (Cp), and Amylase-I (Amy-I), which formed 9 identified alleles and 15 genotypes. All populations had different allele and gene frequency distribution for each locus, which dominated by allele AlbB (0.525), PaB (0.556), CpF (0.608), and Amy-IB (0.639) and by genotype BB (0.312) for Alb loci, BB (0.429) for Pa loci, FS (0.423) for Cp loci and BB (0.472) for Amy-I. Ongole Grade cattle population in this study showed deviation in Hardy-Weinberg Equilibrium (HWE) (P<0.05) for Blora, Kebumen, Semarang, and Kudus, while the rest populations showed in HWE condition. Average heterozygosity and genetic distance of the Ongole Grade cattle population in the recent study were range 0.328-0.529 (for Magelang and Kebumen populations, respectively) and 0.0057-0.0955 (for the Rembang-Kebumen population and Magelang-Kebumen population), respectively. In conclusion, Ongole Grade cattle population in Central Java had high genetic diversity and was divided into two major clusters.